Economic Recessions and Infant Mortality in the U.S., 1999-2008 - Bishai, David; Li, Qingfeng; Ma, Sai (International Journal of Child Health and Nutrition, 2014)
Objectives: Prior studies of US data from the 1990s have shown that economic growth is associated with higher all cause mortality. This paper updates prior findings to more recent data on US infant mortality for blacks and whites. Methods: We analyzed data from 50 US states from 1999 to 2008 using state fixed-effects regression models stratified to identify the racially disparate impact of each state’s economic performance on infant mortality, controlling for state policy-related variables, reflecting population,% black, % on TANF, % on Medicaid, and alcohol consumption. Results: Economic recessions are significantly associated with lower post-neonatal mortality for white infants, but not black infants. Each 1% decrement a state’s gross state product, would be associated with an approximately 2.3 fewer infant deaths (95% CI: -0.294-4.894) in an average state with 64,000 total births. Results were robust to the inclusion of state trends, national trends, state fixed effects, lagged gross state product, and the inclusion of measures of unemployment and state policy variables. Conclusions: This study in combination with studies from the 1990s reflects growing evidence that economic growth in the US can be harmful to child health. Policy makers need to be informed and mindful about the “side effects” of economic growth on health.